(untitled) (International Journal of Engineering Materials and Manufacture, 2021)
This research reports on the suitability of Agricultural bi-products as low temperature thermal insulating materials to replace synthetic insulating materials like polyurethane used in food warmers and ice coolers. Coir and sugarcane bagasse chosen for this research was based on literature review and local availability of materials. Coir was obtained from Badagry, Lagos State and Sugarcane bagasse obtained from Batati, Niger State, the materials were washed, sun dried for three days and cut into smaller pieces before being blended into smaller particles using an electric blender. The blended materials (Coir and Bagasse) were sieved into two different sieve size of 0.5 mm and 1.0 mm respectively. The particles sizes were then combined into blend ratios of 50/50, 60/40, and 70/30 using Gum Arabic as binder. Thermal conductivity test showed that 1.0 mm particle size coir mixed with sugarcane bagasse has the lowest thermal conductivity of 0.01467 W/mK whilst that of 0.5 mm particle size has thermal conductivity of 0.01472 W/mK this is lower compared to the measured thermal conductivity of the polyurethane control sample of 0.01832 W/mK. Sample F (1.0 mm particle size,70% coir and 30% bagasse) with a thermal diffusivity of 5.15 mÂ²/s, water absorption capacity of 410 %, UTS of 0.219 MPa, Compressive strength of 0.583 MPa, Specific heat capacity of 1141.3 J/kgK and thermal resistivity of 68.16 W/m/K is most suitable replacement for polyurethane as low temperature thermal insulator. This is corroborated by the performance evaluation test with carried out between polyurethane lined food warmer and bio-composite lined food warmer. The two test samples have close ice melt rate values and the polyurethane slightly edge the Bio-composite insulating material by 1.2 % in efficiency. The edge in efficiency can be accepted as all materials used in the development of the bio-composite insulating material are completely bio-degradable and environmentally friendly.